Translation, rewriting and formation of Singapore's bilingual education policy : a comparison of English and Chinese editions of "My lifelong challenge : Singapore's bilingual journey" by Lee Kuan Yew - Toh, Wenqi (2017)
It is inevitable that individuals have their own perspective of Singapore’s bilingual education policy, especially those that experienced its formation and history from the pre-independence days of 1950s to the 1980s. The publishing of “My Lifelong Challenge: Singapore’s Bilingual Journey” Singapore’s founding Prime Minister, Mr. Lee Kuan Yew provides information and insights to this part of history. Through the comparison of the English and Chinese editions, this paper discusses the poetics, patronage and ideological differences, which suggest the reasons for the translation and rewriting by Mr. Lee in the Chinese edition. It suggests that the author, Mr. Lee’s different intentions for the English and Chinese editions towards the respective readerships. A reader tends to read either the English or Chinese edition, depending on his dominant language. Towards the English readership, this paper concludes that the author’s intention is more of for them to gain knowledge of this part of Singapore’s history, and to emphasize the importance of the mother tongue. To the Chinese readership that are likely to have certain misunderstanding towards the Government, the Chinese edition serves to address these issues from the author’s perspective, in the hope of seeking these readers’ understanding and if possible, gain their support towards the bilingual policy.